Answer:
B. 2
Explanation:
We know when line 1 is perpendicular to line 2 so m1 × m2 = — 1
(m=slope)
so here we know that the slope of the new line is m2=1
and also line 2 cuts line 1 on a point such that (x,—x)
so we take a look at m2 and (x,—x) & (2,4) :
![we \: have \: \: m2 = 1 \\ so \\ m2 = ( - x - 4)/(x - 2) = 1 \\ \\ x = - 1 \\](https://img.qammunity.org/2022/formulas/mathematics/college/6xprt04zaujzku28owjuxffriu9p9ocbpx.png)
so (x,—x) will be ( —1,1)
now we know that line 2 passes through the point (—1,1)
now put the point as x & y :
![y = x + b \\ 1 = - 1 + b \\ b = 2](https://img.qammunity.org/2022/formulas/mathematics/college/m2cn6083ys4a7nvvlgvhcmlewx7zuqgrfg.png)
so the final answer is 2